Improving wireless Snoop performance using fake ACK technique - Furat Asmat, Moojid; Mohamed Hadi, Habaebi; Borhanuddin, Mohd Ali, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/